"It's a lot more complicated than it seems": physiotherapists' experiences of using compensation strategies in people with Parkinson's - Sheemah Alenezi; Sheemah Alenezi; Sarah Morgan-Trimmer; Sophia Hulbert; William Young; Victoria A. Goodwin (Frontiers Media S.A., 2023)
BackgroundGait disturbances often result in functional limitations in daily activities and negatively impact the quality of life in people with Parkinson's disease. Physiotherapists often employ compensation strategies in an attempt to improve patients' walking. However, little is known about physiotherapists' experiences in this regard. We evaluated how physiotherapists adopt compensation strategies and what they draw on to inform their clinical decision-making.MethodsWe carried out semi-structured online interviews with 13 physiotherapists with current or recent experience working with people with Parkinson's disease in the United Kingdom. Interviews were digitally recorded and transcribed verbatim. Thematic analysis was utilized.ResultsTwo main themes were developed from the data. The first theme, optimizing compensation strategies through personalized care, shows how physiotherapists accounted for the individual needs and characteristics of people with Parkinson's, which resulted in them individually tailoring compensation strategies. The second theme, delivering compensation strategies effectively, considers the available support and perceived challenges with work settings and experience that impact physiotherapists' ability to deliver compensation strategies.DiscussionAlthough physiotherapists strived to optimize compensation strategies, there was a lack of formal training in this area, and their knowledge was primarily acquired from peers. Furthermore, a lack of specific knowledge on Parkinson's can impact physiotherapists' confidence in maintaining person-centered rehabilitation. However, the question that remains to be answered is what accessible training could address the knowledge-practice gap to contribute to the delivery of better-personalized care for people with Parkinson's.